The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0960327114558889
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of antioxidant therapy against oxidative stress and androgen rise in ethylene glycol induced nephrolithiasis in Wistar rats

Abstract: Administration of natural antioxidants has been used to protect against nephrolithiasis. Urolithiasis was induced by ethylene glycol (EG) in Wistar rats. For 4 weeks, group 1 (control) was fed with a standard commercial diet. Group 2 received the same diet with 0.75% of EG. Group 3 received EG plus the diet and water added with antioxidant nutrients and lime juice as the dietary source of citrate (EG + AX). Group 4 same as group 3 with no EG in water. For 8 weeks, group 5 was fed the standard diet wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Our results showed that EG causes the formation of stones in all parts of kidney (cortex, medulla, and para cortex [juxtamedulla]). Th ese results are consistent with other recent studies (Naghii et al 2015;Kandhare et al 2015;Shukla et al 2014;Cho et al 2014). Th e main mechanism of stone formation following administration of EG is related to EG metabolism pathway.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that EG causes the formation of stones in all parts of kidney (cortex, medulla, and para cortex [juxtamedulla]). Th ese results are consistent with other recent studies (Naghii et al 2015;Kandhare et al 2015;Shukla et al 2014;Cho et al 2014). Th e main mechanism of stone formation following administration of EG is related to EG metabolism pathway.…”
Section: Discussionsupporting
confidence: 92%
“…It immediately binds to Calcium in tissues and urinary tract and forms kidney stones (Atakan et al 2007). Results of Naghii et al (2015) showed that two other mechanisms that contribute to the stone formation include elevated androgen levels in plasma following administration of EG as well as oxidative stress in the kidney that causes apoptosis in renal tubular epithelial cells and this process is one of the most important factors in kidney stone cascade event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) . (Tugcu et al, 2008;Parmar et al, 2012;Makasana et al, 2014;Naghii et al, 2014;Kumar et al, 2015 (Giebisch, 2004;Goff, 2004;Grunberg et al, 2006;Grunberg et al, 2011;Constable et al, 2013;) . (Aviram et al, 2002;Touhami et al, 2007 (Karadi et al, 2006;Celik et al, 2007) .…”
mentioning
confidence: 99%